Efeitos do estresse por frio em frangos de corte na fase inicial de criação - Cátia Borges Ferreira (2017)
The study was conducted to evaluate the effects of cold stress in broiler chicks from one to 21 days of age, on performance, organs development, enzymatic activity (lipase, amylase and total protein), physiological parameters (respiratory rate and rectal temperature), heterophil/ lymphocyte ratio and feed metabolizability. A total of 720 birds were distributed randomly into four climatic chambers, each containing six cages, and the cage holds, initially, 30 chicks each. The treatments were defined by the temperature, in which each climatic chamber created distinct thermal environments according to the age of the birds, for the 1st, 2nd and 3rd weeks, respectively, as follows: Comfort I- 33, 30 and 27°C; Comfort II 30, 27 and 24°C; Moderate Cold Stress 24, 21 and 18°C; Intense Cold Stress 22, 19 and 16°C. During the first 21 days of age, the birds submitted to moderate and intense stress temperatures had the lowest weight gain and the worst feed conversion. The organs relative weights also were affected by the two stress treatments, resulting in a higher heart relative weight for the moderate and intense stress during the experiment period. The lungs and pancreas had the highest relative weight on the third week, with the stress treatments as well. The cold stress also affected the heretophile/lymphocyte ratio, on the first two weeks. The ratio was higher when the birds where submitted to moderate and intense cold stress. However, the temperature differences did not affect the enzyme activity. In conclusion, the temperatures below the comfort zone of broiler chicks on the first three weeks of age result in stress, affecting their performance, development, physiological and hematological standards.